Inequality within the UK: An economic analysis. - James Carey (2012)
With inequalities in earnings, employment and economic activity widespread throughout the UK, this thesis examines these inequalities and attempts to explain them. Data from the Living in Wales survey and the Annual Population Survey is used to examine the earnings response to unemployment in the UK, with particular attention paid to Wales and its position relative to other UK regions. Strong evidence of a wage curve is found, and this wage curve is tested over the earnings distribution and levels of centralization. The returns to degrees, masters and PhDs are investigated, with a focus on how returns vary over regions. Large differences are found using a national baseline, but these differences are greatly reduced when regional differences are controlled for. The use of quantile regression techniques suggests that the graduate premium varies little over the earnings distribution. The inequalities m earnings, employment and economic activity are broken down into a component of individual characteristics and a component of area effects. It is found that area effects play a small role, with inequalities driven by individual characteristics. These individual effects are also broken down, with occupation identified as the key driver of inequalities.